Spinal ependymoma in adults: from molecular advances to new treatment perspectives - Cerretti, Giulia; Pessina, Federico; Franceschi, Enrico; Barresi, Valeria; Salvalaggio, Alessandro; Padovan, Marta; Manara, Renzo; Di Nunno, Vincenzo; Bono, Beatrice Claudia; Librizzi, Giovanni; Caccese, Mario; Scorsetti, Marta; et al. (Frontiers in Oncology, 2023)
Ependymomas are rare glial tumors with clinical and biological heterogeneity, categorized into supratentorial ependymoma, posterior fossa ependymoma, and spinal cord ependymoma, according to anatomical localization. Spinal ependymoma comprises four different types: spinal ependymoma, spinal ependymoma MYCN-amplified, myxopapillary ependymoma, and subependymoma. The clinical onset largely depends on the spinal location of the tumor. Both non-specific and specific sensory and/or motor symptoms can be present. Owing to diverse features and the low incidence of spinal ependymomas, most of the current clinical management is derived from small retrospective studies, particularly in adults. Treatment involves primarily surgical resection, aiming at maximal safe resection. The use of radiotherapy remains controversial and the optimal dose has not been established; it is usually considered after subtotal resection for WHO grade 2 ependymoma and for WHO grade 3 ependymoma regardless of the extent of resection. There are limited systemic treatments available, with limited durable results and modest improvement in progression-free survival. Thus, chemotherapy is usually reserved for recurrent cases where resection and/or radiation is not feasible. Recently, a combination of temozolomide and lapatinib has shown modest results with a median progression-free survival (PFS) of 7.8 months in recurrent spinal ependymomas. Other studies have explored the use of temozolomide, platinum compounds, etoposide, and bevacizumab, but standard treatment options have not yet been defined. New treatment options with targeted treatments and immunotherapy are being investigated. Neurological and supportive care are crucial, even in the early stages. Post-surgical rehabilitation can improve the consequences of surgery and maintain a good quality of life, especially in young patients with long life expectancy. Here, we focus on the diagnosis and treatment recommendations for adults with spinal ependymoma, and discuss recent molecular advances and new treatment perspectives.